The return of vertebrate and invertebrate fauna to bauxite mined areas in Australia - Majer, Jonathan; Nichols, O.; Wykes, B. (1989)
The jarrah EucalYptus marginata forest of Western Australia occupies approximately 1.75 million ha of the south-western corner of the State. Most of the State's population of 1.5 million people live in the south-west and there are pressures on the forest to support a number of land-uses, such as water catchment, timber production, recreation, honey production and conservation. In this Chapter we discuss the evolution of Government environmental requirements, together with fauna research and rehabilitation techniques since the commencement of mining.